Meta-analysis of the utility of culture, biopsy, and direct KOH examination for the diagnosis of onychomycosis (2017)
Background: Onychomycosis is a highly prevalent disease worldwide. There is no standard test for its diagnosis, which remains costly, wasteful, and is sometimes delayed. The diagnostic tests for this disease are few and discordant. The objective was to evaluate the diagnostic validity, performance, and accuracy of culture, nail clipping with Periodic. Acid-Schiff –PAS- staining (biopsy), and direct potassium hydroxide (KOH) examination for the study of onychomycosis. Methods: A systematic review was conducted via meta-analysis using 5 databases and 21 search strategies. An ex ante protocol was applied with inclusion and exclusion criteria. Quality was assessed with the Quality Assessment of Diagnostic. Accuracy Studies (QUADAS) tool, and the sensitivity, specificity, predictive values, likelihood ratios, diagnostic, odds ratios, receiver operating characteristic (ROC) curves, and proportion of correctly diagnosed patients were, evaluated with the meta-analysis of studies of evaluations of diagnostic and screening tests (Meta-DiSc) and. Epidat using a random effects model. Results: The efficiency or accuracy of the three tests is influenced by the methodological quality of the studies. These values are lower for KOH and culture and higher for biopsy in moderate quality studies. Conclusion: The diagnostic tests evaluated in this meta-analysis independently showed acceptable validity, performance, and efficiency, with nail clipping with PAS staining outperforming the other two tests.